Sticky Captions: Genre-internal Variation in Print-based Ad Translating - Sidiropoulou, Maria (Meta, 2008)
AbstractThe study shows that source and target versions of ads can accurately mirror linguistic preference across source and target environments. It points to culture-specific, genre-specific and gender-specific linguistic preference imprinted in ad discourses. It examines genre-internal variation in print-based advertising in the English-Greek translation paradigm. It explores variation in discursive preference manifested in target versions of business-oriented and cosmetics ads, with a view to indicating that male and female audiences are attributed different social needs in the target environment. If ST/TTs of ads reflect culture-specific hierarchies of deeply felt needs in a society, a lot can be concluded about the immense power of advertising to register fine distinctions with respect to cultural versions of identities, to mould cultural audiences’ expectations and to create new social values in target environments.